An anti-fault study of basalt fiber reinforced concrete in tunnels crossing a stick-slip fault. Issue 148 (September 2021) - Zeng, Guanxiong; Geng, Ping; Guo, Xiangyu; Li, Peisong; Wang, Qi; Ding, Ti
Abstract: Crossing active faults has proven to cause significant damage in tunnels. In this study, a large–scale plate thrust model stimulating the LongMenShan Fault (LMSF) dislocation was established numerically. The characteristic dislocation curve of the fault generated at the stick-slip incidence was derived. Furthermore, a soil-structure FE model was established with a tunnel structure crossing the LMSF Zone, in which the hanging wall and footwall moved according to the abovementioned dislocation curve. To cope with the serious damage of tunnel caused by fault dislocation, the articulated design was adopted. For discovering an appropriate material to construct the articulated sections and enhance the flexibility of tunnel structure, basalt fiber reinforced concrete (BFRC) was studied by SEM test and mechanical tests. The results showed that basalt fiber could increase the tensile capacity and tenacity of concrete and the 0.5% BFRC was selected as the optimal fiber volume content. By applying the 0.5% BFRC articulated design, the length and width of tunnel cracks generated by fault dislocation decreased by 33.45% and 38.11%, respectively. This study could serve as a reference in the design of fault-crossing tunnel projects. Highlights: The LongMenShan Fault dislocation was analyzed by a large-scale plate thrust model. The crack morphology of the plain concrete tunnel structure was revealed after subjecting to LongMenShan Fault dislocation. The optimal volume content of basalt reinforced fiber concrete was determined through SEM test and mechanical tests. The anti-fault performance of the articulated tunnel constructed by 5% basalt reinforced fiber concrete was estimated.